Ontology Based Classification of Electronic Health Records to Support Value-Based Health Care - Dal Bosco, Avner; Vieira, Renata; Zanotto, Bruna; Etges, Ana Paula Beck da Silva (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2021: Anais da X Brazilian Conference on Intelligent Systems, 2021)
Value-based health care management models require a precise accounting of health indexes such as risk events monitoring, clinical conditions, patient handling and outcomes. Currently this accounting is performed by manually reading and searching through electronic health records for these indexes. Our research proposes a way to make this an autonomous task that is performed by a computer using a Portuguese free-text concept classifier model based on ontologies. To validate our model we tested it on digital clinical records from 191 patients under ischemic stroke care. We have selected 30 management indexes to be identified in these texts. Our model reached, on average 56,8% of f1-score, varying from 5,83% to 94,78% f1-score across different management indexes.